Śląskość „dwóch prędkości” – strona internetowa a przekaz polityczny wybranych organizacji regionalnych na Górnym Śląsku. - Wądołowski, Marcin (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2020)
The article focuses on the relationship between specificity of political associations and quality of their communication on the Internet. This issue has been examined at extreme example of two regional organizations from Upper Silesia – Zwiazek Gornoslaski and Ruch Autonomii Slaska. The author, using self-made research tool, compared the formal content of the communication on official websites. The results of the analysis were assessed with the activity profile and the average age of members examined associations.